Characterization of pre‐analytical sample handling effects on a panel of Alzheimer's disease–related blood‐based biomarkers: Results from the Standardization of Alzheimer's Blood Biomarkers (SABB) working group. Issue 8 (29th November 2021) - Verberk, Inge M. W.; Misdorp, Els O.; Koelewijn, Jannet; Ball, Andrew J.; Blennow, Kaj; Dage, Jeffrey L.; Fandos, Noelia; Hansson, Oskar; Hirtz, Christophe; Janelidze, Shorena; Kang, Sungmin; Kirmess, Kristopher; et al.
Abstract: Introduction: Pre‐analytical sample handling might affect the results of Alzheimer's disease blood‐based biomarkers. We empirically tested variations of common blood collection and handling procedures. Methods: We created sample sets that address the effect of blood collection tube type, and of ethylene diamine tetraacetic acid plasma delayed centrifugation, centrifugation temperature, aliquot volume, delayed storage, and freeze–thawing. We measured amyloid beta (Aβ)42 and 40 peptides with six assays, and Aβ oligomerization‐tendency (OAβ), amyloid precursor protein (APP)699‐711, glial fibrillary acidic protein (GFAP), neurofilament light (NfL), total tau (t‐tau), and phosphorylated tau181. Results: Collection tube type resulted in different values of all assessed markers. Delayed plasma centrifugation and storage affected Aβ and t‐tau; t‐tau was additionally affected by centrifugation temperature. The other markers were resistant to handling variations. Discussion: We constructed a standardized operating procedure for plasma handling, to facilitate introduction of blood‐based biomarkers into the research and clinical settings.